The Effect of Callyspongia Biru Antibacterial Extract Concentration Towards the growth of Bacterial Isolates of Eucheuma cottonii Seaweed with Ice-ice Disease - Masing, Feliksitas Angel (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2021)
This research was conducted at the Biology Education Laboratory, Faculty of Teacher Training and Educational Sciences, Nusa Cendana University, with the aim of knowing the effect of the concentration of the antibacterial extract of Callyspongia biru on the growth of bacteria that caused Ice-ice disease. The method used in this study was an experimental method, with a Completely Randomized Design (CRD) consisting of 4 treatments (concentration of Callyspongia blue extract of 10%, 20%, 30% and 40%) with 3 times repetition. Therefore, the total treatment units were 12 units. The parameter that has been measured in this study was the diameter of the inhibition zone. The inhibition zone diameter data was then analyzed by using one-way ANOVA with the Tukay method.If Fcount Â is greater than Ftable then it would be tested further using Honest Reality Difference test at 5% significant level. The result showed that the different concentrations of Callyspongia blue extract gave significantly different effects on the growth of bacterial isolates from seaweed Eucheuma cottonii with Ice-ice disease. At a concentration of 40%, Callyspongia biru extract showed the strongest average inhibition of 27.67 mm.